Ecto- and Endoparasitic Fungi on Ants from the Holarctic Region - Xavier Espadaler; Sergi Santamaria (Psyche: A Journal of Entomology)
The ant-specific fungi Aegeritella, Laboulbenia, Rickia, Hormiscium, and Myrmicinosporidium in the Holarctic region—nine species—are reviewed. Present knowledge is highly biased geographically, as shows the single record for Holarctic Asia, and this is to solve. The phylogenetic position of Aegeritella, Hormiscium, and Myrmicinosporidium is unknown. Hosts seem to be also skewed phylogenetically although this may be a true pattern.